Innovation, Technology and User Experience in Museums: Insights from Scientific Literature (2020)
Museums play an important role in preserving the heritage and cultural legacy of humanity, however, one of their main weaknesses in regards the user is their static nature. At present, and in the face of the development of diverse technologies and the ease of access to information, museums have upgraded their implementation of technologies aimed at improving the user experience, trying more and more to access younger audiences with a sensitivity and natural capacity for the management of new technologies. This work identifies trends in the use of technological tools by museums worldwide and the effect of these on the user or visitor experience through a review of scientific literature. To complete the work, we performed a search of the publications in the Scopus® referencing database, and downloaded, processed, and visualized the data using the VOSviewer® tool. The main trends identified in this context of analysis are related to the role of museums with the development and improvement of the user experience; orientation to young audiences and innovation driven by the user through Interactive Systems, digital games, QR Codes, apps, augmented reality, virtual reality and gamification, among others. The objective of the implementation of new technologies in the context of museums is to satisfy the needs of contemporary communication, for all types of content and aimed at an increasingly digital audience, in order to ensure positive interaction and feedback from ideas with social and cultural changes.